Gut microbiota and obesity-associated osteoarthritis. Issue 9 (September 2019) - Liu, Y.; Ding, W.; Wang, H.L.; Dai, L.L.; Zong, W.H.; Wang, Y.Z.; Bi, J.; Han, W.; Dong, G.J.
Summary: Obesity is a well-known primary risk factor for osteoarthritis (OA). In recent decades, the biomechanics-based theoretical paradigm for the pathogenesis of obesity-associated OA has been gradually but fundamentally modified. This modification is a result of accumulating evidence that biological factors also contribute to the etiology of the disease. The gut microbiota is a complicated ecosystem that profoundly influences the health of the host and can be modulated by the combined effects of environmental stimuli and genetic factors. Recently, enteric dysbacteriosis has been identified as a causal factor in the initiation and propagation of obesity-associated OA in animal models. Gut microbes and their components, microbe-associated lipid metabolites, and OA interact at both systemic and local levels through mechanisms that involve interplay with the innate immune system. However, the demonstration of causality in humans will require further studies. Nonetheless, probiotics, prebiotics, dietary habits and exercise, which aid the restoration of a healthy microbial community, are potential therapeutic approaches in the treatment of obesity-associated OA.